Thyroid dysfunction in Down's syndrome secondary to risperidone. Issue 4 (8th November 2022) - Shaddel, Farshad; Lockstone, Matthew
Abstract : Here, the authors discuss a patient with mild intellectual disability and Down's syndrome who appeared to experience deterioration in her well controlled thyroid function twice, secondary to higher dosages of risperidone for treatment of her delusional disorder. The case therefore suggests that thyroid function monitoring may be of value in individuals predisposed to thyroid dysfunction who are commenced on antipsychotic therapy, especially risperidone.